Influence of preoperative sodium concentration on outcome of patients with hepatitis B virus cirrhosis after liver transplantation. Issue 10 (October 2016) - Wang, Peijie; Huang, Gang; Tam, Ngalei; Wu, Chenglin; Fu, Shunjun; Hughes, Bridget P.; Wu, Linwei; He, Xiaoshun
Abstract : Objectives: Whether preoperative serum sodium concentration could influence post-transplant patients' prognosis remains controversial. The aim of this study was to evaluate the influence of patients' pretransplant sodium concentration on the prognosis after liver transplantation in a cohort of patients with hepatitis B virus-related cirrhosis. Patients and methods: Data derived from the Chinese Liver Transplantation Registry system from 1 January 2000 to 31 December 2011 were extracted. The serum sodium concentrations and model for end-stage liver disease scores were recorded at listing before liver transplantation, and the relationship between the above parameters and patients' outcome was analyzed. Results: A total of 2733 patients were included in this study. Compared with patients in the normal group (serum sodium between 135 and 150 mmol/l), patients in the severe hyponatremia group (<125 mmol/l) ( P =0.022) and hypernatremia group (>150 mmol/l) ( P =0.008) had a poorer prognosis. No significant differences were found among the moderate hyponatremia group (125–130 mmol/l) ( P =0.113) and the mild hyponatremia group (130–135 mmol/l) ( P =0.461). The 5-year cumulative survivals for the hyponatremia (⩽135 mmol/l), normal (135–150 mmol/l), and hypernatremia (≥150 mmol/l) pretransplant group are 79.52, 82.23, and 69.30%, respectively. Conclusion: Our analysis showed that for patients with hepatitis B virus-related cirrhosis in mainland China, patients with abnormal serum sodium concentrations have poorer prognosis; both preoperative hyponatremia and hypernatremia were identified as negative risk factors for patients' outcome.